Redescription and molecular characterization of two Trichodina species (Ciliophora, Peritrichia, Mobilida) from freshwater fish in China. (February 2022) - Wang, Zhe; Liu, Mingjian; Ma, Hongang; Lu, Borong; Shen, Zhuo; Mu, Changjun; Alfarraj, Saleh A.; El-Serehy, Hamed A.; Warren, Alan
Abstract: During an investigation of parasitic ciliates in northern China, two Trichodina species, T. acuta Lom, 1970 and T. nigra Lom, 1960, were isolated from the freshwater fish Cyprinus carpio Linnaeus, 1758. The morphology of each species was investigated based on dry silver nitrate-stained specimens. In addition, the molecular phylogeny of each was analyzed based on small subunit ribosomal DNA (SSU rDNA) sequence data. Trichodina acuta can be distinguished from its congeners by the undefined periphery of the central circle, the distinct gap between the rays and the central circle, and the distinctly sickle-shaped blades. Trichodina nigra is a cosmopolitan ciliate and is characterized by its densely linked denticles, broad, rounded spatula-shaped blades, robust central parts, and well developed rays. Phylogenetic analyses revealed that T. acuta and T. nigra nest within different clades, supporting the assertion that the GC content of SSU rDNA sequences could reflect evolutionary relationships among Trichodina species. Graphical abstract: Unlabelled Image